Mathematical modeling of laser-assisted deep drawing - Kreis, Oliver; Hein, Philipp (Journal of Materials Processing Technology, 2001)
Although laser manufacturing with material removal (cutting) and with material addition (welding, rapid prototyping) has reached a high degree of industrial maturity, processes with constant mass and volume as forming techniques did not find a broad application up to now with the exception of laser bending. For efficient workpiece shaping the laser is not used as the sole source of energy but rather for a selective weakening of the workpiece in those regions, where strong deformations are achieved conventionally by mechanical forces. A first application of the latter idea is deep drawing, where laser beams weaken the material near the drawing edge, where the material is bent. Thus, a beneficial reduction of the drawing force is obtained, also allowing processing of materials, that are difficult to draw due to their low ductility. To predict the upper limit for the reduction of drawing forces, mathematical modeling of the process is necessary. Experiments have shown that a reduction of the drawing force up to 25% can easily be achieved. A mathematical analysis of laser-assisted deep drawing carried out recently is presented in the actual paper and shows that even much larger reductions are feasible. © 2001 Elsevier Science B.V. All rights reserved.
Keywords: Deep drawing; Laser materials processing